2015
DOI: 10.1016/j.expneurol.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Optimized methods for epilepsy therapy development using an etiologically realistic model of focal epilepsy in the rat

Abstract: Conventionally developed antiseizure drugs fail to control epileptic seizures in about 30% of patients, and no treatment prevents epilepsy. New etiologically realistic, syndrome-specific epilepsy models are expected to identify better treatments by capturing currently unknown ictogenic and epileptogenic mechanisms that operate in the corresponding patient populations. Additionally, the use of electrocorticography permits better monitoring of epileptogenesis and the full spectrum of acquired seizures, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Several independent laboratories have successfully deployed FPI, and induced various forms of convulsive and non-convulsive epileptic seizures. Our laboratory has focused on developing, characterizing and optimizing a rat model of focal neocortical non-convulsive PTE induced by rostral parasagittal FPI (rpFPI; Curia et al, 2011;D'Ambrosio et al, 2004;Eastman et al, 2015), and deploying it to test treatments (Eastman et al, 2010;D'Ambrosio et al, 2013;Curia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several independent laboratories have successfully deployed FPI, and induced various forms of convulsive and non-convulsive epileptic seizures. Our laboratory has focused on developing, characterizing and optimizing a rat model of focal neocortical non-convulsive PTE induced by rostral parasagittal FPI (rpFPI; Curia et al, 2011;D'Ambrosio et al, 2004;Eastman et al, 2015), and deploying it to test treatments (Eastman et al, 2010;D'Ambrosio et al, 2013;Curia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The extensive EEG coverage used in this study, including the frontal lobes bilaterally, should have identified frontal‐onset seizures if they occurred. Montages consisting of four electrodes versus two have been shown to more reliably detect seizures after FPI; therefore, the 16 electrodes used here should be extremely reliable for detecting seizure onset. A 10 s cutoff was used to define ictal events because of concerns voiced in the animal literature about whether shorter events are epileptic seizures, even though we are well aware that seizures in patients and animal studies can last <10 s .…”
Section: Discussionmentioning
confidence: 98%
“…Heat, trauma, and chronic compression of underlying brain tissue are the main promoters of unintended brain injury during electrode implantation. Heat can be produced during drilling and during the highly exothermic curing of the dental acrylic from which the headset is constructed . To dissipate the frictional heat generated during drilling, the skull and drill bit can be cooled continuously with sterile saline maintained at room temperature.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Heat can be produced during drilling and during the highly exothermic curing of the dental acrylic from which the headset is constructed. [23][24][25] To dissipate the frictional heat generated during drilling, the skull and drill bit can be cooled continuously with sterile saline maintained at room temperature. To dissipate the heat associated with curing, a continuous stream of cool air may be directed onto the hardening acrylic and/or alcohol can be used for evaporative cooling.…”
Section: Protecting the Brain During Epidural Electrode Implantationmentioning
confidence: 99%